RETROSPECTIVE STUDY OF BONE RESORPTION RATES OF DENTAL IMPLANTS IN RELATION TO THE TIME OF INSERTION: IMMEDIATE VERSUS DELAYED - Cosmin Ionuț Lixandru (Romanian Journal of Oral Rehabilitation)
Aim of the study: Comparative evaluation of the degree of bone resorption between implants inserted immediately after tooth extraction and delayed implants, in correlation with other influencing factors. Materials and methods: The present study is a retrospective study that was carried out between January 1, 2016 and December 31, 2023, which involved a thorough analysis of the medical files belonging to patients who benefited from complex implanto-prosthetic reconstructions during this time period. The study analyzed a number of 268 implants applied to patients who met the inclusion criteria in the study, at the level of which measurements were made immediately after the surgical intervention and 6 months after the prosthetic restoration. Results: The moment chosen for the insertion of dental implants represents an aspect that must be analyzed with extreme care. Our research reveals significantly lower bone resorption for implants inserted immediately after tooth extraction in all planes studied. Conclusions Complex implanto-prosthetic rehabilitations must be promoted and currently constitute the ideal form of treatment for the rehabilitation of edentulous patients and, of course, increasing their quality of life.